Towards 90-90-90 Target: Factors Influencing Availability, Access, and Utilization of HIV Services—A Qualitative Study in 19 Ugandan Districts - Bajunirwe, Francis; Tumwebaze, Flora; Akakimpa, Denis; Kityo, Cissy; Mugyenyi, Peter; Abongomera, George (BioMed research international, 2018)
UNAIDS has set a new target 90-90-90 by 2020. To achieve this target, current programs need to address challenges that limit access, availability, and utilization of HIV testing and treatment services. Therefore, the aim of this study was to identify the barriers that influence access, availability, and utilization of HIV services in rural Uganda within the setting of a large donor funded program. Methods.We conducted key informant interviews with stakeholders at the district level, staff of existingHIV/AIDS projects, and health facilities in 19 districts. Data were also collected from focus group discussions comprised of clients presenting for HIV care and treatment. Data were transcribed and analyzed using content analysis. Results. Barriers identified were as follows: (1) drug shortages including antiretroviral drugs at health facilities. Some patients were afraid to start ART because of worrying about shortages (2) distance (3) staffing shortages; (4) stigma persistence; (5) lack of social and economic support initiatives that enhance retention in treatment. Conclusions. In conclusion, our study has identified several factors that influence access, availability, and utilization of HIV services. Programs need to address drug and staff shortages, HIV stigma, and long distances to health facilities to broaden access and utilization in order to realize the UNAIDS target
Keywords: Antiretroviral therapy (ART); Uganda